Pengembangan E-LKPD untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Peserta Didik pada Materi Bangun Ruang Sisi Lengkung - Sarman, Afriano Andri; Suastika, I Ketut; Murniasih, Tatik Retno (Jurnal Tadris Matematika, 2023)
This research aims to develop a valid, practical, and effective electronic student worksheet based on Liveworksheets that can enhance students’ mathematical problem-solving abilities. The indicator for these abilities include problem identification, procedure design, problem-solving, and conclusion drawing. The research and development of these electronic student worksheets have the benefit of providing interactive teaching materials for mathematics learning. The ADDIE development model was used in this research and development process. The research instruments include expert validations sheets, teacher and student response questionnaires were employed to measure practicality. The effectiveness of the electronic student worksheet was evaluated based on activity scores, response scores, and student test scores. The validity percentage of this electronic student worksheet was 78.67% for materials and 90% for media. The practicality of the electronic student electronic student worksheet was determined through the percentage of positive responses, with 96% from teacher and 84.33% from students. The average student activity score was 55.12, the response score was 45.06, and the student test score was 68.08. The electronic student worksheet developed in this study successfully enhanced students’ mathematical problem-solving abilities according to the predefined indicators.